Under new management : universities, administrative labor, and the professional turn - Martin, Randy, 1957-2015 (Temple University Press, 2011)
Faculty members who care about the institutions of higher education where they work are often at odds with university management. In his forceful book, Under New Management, Randy Martin takes a novel, evenhanded approach to this gulf between professors, who feel a loss of autonomy, and administrators. Martin imagines a political future for academic labor based on a critical understanding of the administrative work that faculty already undertake. He considers the differences between self-rule and specialized expertise and provides a case study of a New York City public school to show how kids and families respond to the demands of managerial productivity that is part of preparing students for college. Under New Management also considers changes faced by students, faculty, and administrators in light of this reworked social compact of professionals.